Low interest rate environment amplifies negative effects of austerity policy - Mathias Klein (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Large-scale fiscal consolidations and the implementation of structural reforms should help southern European countries resolve the crisis. But recent studies indicate that in conjunction with the low interest rate in the euro area, the austerity measures that has been imposed could have the opposite effect, leading to an increase in sovereign debt and economic slowdown. For this reason, a more balanced policy mix consisting of less restrictive spending measures and more investment incentives is preferable to an austere savings policy.
Keywords: 330